Eksperimentasi Permainan Bisik Berantai dalam Meningkatkan Maharah Istima dan Kalam Siswa Kelas VIII MTs Nurul Ummah Kotagede Yogyakarta - Nurul Huda; Eka Utari Handayani (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, 2019)
The background of this research is the low value of istima' maharah scores and kalam in Arabic lessons at MTs Nurul Ummah related to the creativity of teachers' creativity in teaching, there is no training on four language proficiency, teacher development, and methods used by conventional method teachers. The purpose of this study was to study the increase in the value of maharah istima' and kalam with serial whisper games and the difference in values ​​between the experimental class and the control class. This research is field research using quantitative research and experimental methods. The results of this study prove an increase in istima' maharah scores and kalam in the experimental class from pre-action and post-action. Measurement results of istima' maharah pretest and posttest 'Increase the average value of 25.83. On increasing, maharah kalam increased by 25. The results of the analysis can be concluded from the whisper chain game can increase maharah istima' and kalam. Based on the results of the t-test, the value (maharah istima') sig. (2-tailed) = 0.008 so the value of sig. (2-tailed) <0.050 and the value of kalam maharah based on 0,000, so the value of sig (2-tailed) <0.050, which means that it is meant by significant for istima' maharah and kalam maharah after giving assistance with serial whisper media.